Functional network connectivity impairments and core cognitive deficits in schizophrenia. Issue 16 (16th July 2019) - Adhikari, Bhim M.; Hong, L. Elliot; Sampath, Hemalatha; Chiappelli, Joshua; Jahanshad, Neda; Thompson, Paul M.; Rowland, Laura M.; Calhoun, Vince D.; Du, Xiaoming; Chen, Shuo; Kochunov, Peter
Abstract: Cognitive deficits contribute to functional disability in patients with schizophrenia and may be related to altered functional networks that serve cognition. We evaluated the integrity of major functional networks and assessed their role in supporting two cognitive functions affected in schizophrenia: processing speed (PS) and working memory (WM). Resting‐state functional magnetic resonance imaging (rsfMRI) data, N = 261 patients and 327 controls, were aggregated from three independent cohorts and evaluated using Enhancing NeuroImaging Genetics through Meta Analysis rsfMRI analysis pipeline. Meta‐ and mega‐analyses were used to evaluate patient‐control differences in functional connectivity (FC) measures. Canonical correlation analysis was used to study the association between cognitive deficits and FC measures. Patients showed consistent patterns of cognitive and resting‐state FC (rsFC) deficits across three cohorts. Patient‐control differences in rsFC calculated using seed‐based and dual‐regression approaches were consistent (Cohen's d : 0.31 ± 0.09 and 0.29 ± 0.08, p  < 10 −4 ). RsFC measures explained 12–17% of the individual variations in PS and WM in the full sample and in patients and controls separately, with the strongest correlations found in salience, auditory, somatosensory, and default‐mode networks. The pattern of association between rsFC ( within‐network ) and PS ( r = .45, p = .07) and WM ( r = .36, p = .16), and rsFC ( between‐network ) and PS ( r = .52, p = 8.4 × 10 −3 ) and WM ( r = .47, p = .02), derived from multiple networks was related to effect size of patient‐control differences in the functional networks. No association was detected between rsFC and current medication dose or psychosis ratings. Patients demonstrated significant reduction in several FC networks that may partially underlie some of the core neurocognitive deficits in schizophrenia. The strength of connectivity‐cognition relationships in different networks was strongly associated with network's vulnerability to schizophrenia.